TEACHING ENGLISH IN INDONESIAN PRIMARY SCHOOLS: THE MISSING LINK - Santhy Hawanti (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2011)
One of the rationales of teaching English in primary schools is to motivate students‘interest in English language learning. There are two keywords underpin this idea; motivation and interest. To be able to motivate and attract students‘interest in learning English, teachers are required to create interesting teaching and learning process. Some techniques are proposed to work with this idea, such as teaching English through games, sing songs, role play or telling story. These activities are expected help teachers to create enjoyable teaching atmosphere for their students and maintain their learning motivation. However, there seems to be a contradictory situation faced by the teachers in relation to their teaching English. Teachers have to test the students to measure their achievements. Their achievements will be an instrument to justify whether the teaching of English is successful or not. Now, the objective of learning has turned its direction, not again to motivate the students but more to force the students to achieve a particular standard. Teaching is not created to attract interest but it creates to make students able to do the test. There is a missing link. To deal with this problem, one way teachers might do is to change or alter the test form, not focused in a written form but it might be presented in more interactive way.